Poliomyelitis amidst the COVID-19 pandemic in Africa: Efforts, challenges and recommendations - Olivier Uwishema; Emmanuel Ebuka Elebesunu; Oumnia Bouaddi; Arushi Kapoor; Samaa Akhtar; Fortune Benjamin Effiong; Adhiraj Chaudhary; Helen Onyeaka (Elsevier, 2022)
Poliomyelitis is the leading infectious cause of acute flaccid paralysis among children under five years of age, caused by the Wild Poliovirus, with no medical cure other than prevention through vaccination. The advent of mass vaccination campaigns against polio disease worldwide has greatly decreased the number of global cases and limited the rate of transmission. However, the emergence of Vaccine-derived Poliovirus due to genetic reversions in the live attenuated oral polio vaccine has posed a significant impediment to global polio eradication efforts. Therefore, There is a need to modify the vaccination regimen by utilizing more doses of inactivated poliovirus vaccine or adopting the bivalent oral polio vaccine in order to eliminate the transmission of Vaccine-derived Poliovirus. In addition, collective efforts from governments, health policymakers, vaccination groups and health-related bodies are required to improve vaccine coverage and suppress the circulation of Vaccine-derived Poliovirus.